Exciton dynamics in conjugated polymer systems - Barford, William (Frontiers in Physics, 2022)
Exciton dynamics in pi-conjugated polymers systems encompass multiple time and length scales. Ultrafast femtosecond processes are intrachain and involve a quantum mechanical correlation of the exciton and nuclear degrees of freedom. In contrast, post-picosecond processes involve the incoherent F\"orster transfer of excitons between polymer chains. Exciton dynamics is also strongly determined by the spatial and temporal disorder that is ubiquitous in conjugated polymers. Since excitons are delocalized over hundreds of atoms, a theoretical understanding of these processes is only realistically possible by employing suitably parametrized coarse-grained exciton-phonon models. Moreover, to correctly account for ultrafast processes, the exciton and phonon modes must be treated on the same quantum mechanical basis and the Ehrenfest approximation must be abandoned. This further implies that sophisticated numerical techniques must be employed to solve these models. This review describes our current theoretical understanding of exciton dynamics in conjugated polymer systems. We begin by describing the energetic and spatial distribution of excitons in disordered polymer systems, and define the crucial concept of a `chromophore' in conjugated polymers. We also discuss the role of exciton-nuclear coupling, emphasizing the distinction between `fast' and `slow' nuclear degrees of freedom in determining `self-trapping' and `self-localization' of exciton-polarons. Next, we discuss ultrafast intrachain exciton decoherence caused by exciton-phonon entanglement, which leads to fluorescence depolarization on the timescale of 10-fs. Interactions of the polymer with its environment causes the stochastic relaxation and localization of high-energy delocalized excitons onto chromophores. The coupling of excitons with torsional modes also leads to various dynamical processes. On sub-ps timescales it causes exciton-polaron formation (i.e., exciton localization and local polymer planarization). Conversely, on post-ps timescales stochastic torsional fluctuations cause exciton-polaron diffusion along the polymer chain and at higher temperatures to transient exciton delocalization via extended exciton states. We next describe a first-principles, F\"orster-type model of interchain exciton transfer and diffusion in the condensed phase, whose starting point is a realistic description of the donor and acceptor chromophores. Finally, we discuss condensed phase transient exciton delocalization in highly-ordered nanofibers. We survey experimental results and explain how they can be understood in terms of our theoretical description of exciton dynamics.